(untitled) (Research, Society and Development, 2021)
Studies on changes in morphological features are important to understand the functioning of a river system. This research aimed to evaluate the evolution of the morphological features, the lateral migration in the lower course of the Cabaçal river, Mato Grosso. To characterize the environmental elements, the cartographic basis of the RADAMBRASIL project (1982) was used. To analyze the alterations of the morphological features in the low course of the Cabaçal river, LANDSAT images from the years 1984 and 2018 were used. For making the temporal maps, the ArcGis 10.1 and Spring 5.2 software were used. Over the course of 34 years, the number of bays and lagoons has increased, intensification of the sedimentation process with the appearance and sediment bars. The morphological features recorded in 1984 in compartments l, ll and lll were 57 bays, 345 lagoons and 13 sediment bars; in 2018, 61 bays, 502 lagoons, 50 sediment bars and seven river islands were computed. The research presented the spatial changes generating relevant information about the low course of Cabaçal, being able to subsidize measures of recovery and preservation of the basin.